2023
DOI: 10.1038/s41557-023-01221-1
|View full text |Cite
|
Sign up to set email alerts
|

Fibril formation and ordering of disordered FUS LC driven by hydrophobic interactions

Abstract: Biomolecular condensates, protein-rich and dynamic membrane-less organelles, play critical roles in a range of subcellular processes, including membrane trafficking and transcriptional regulation. However, aberrant phase transitions of intrinsically disordered proteins in biomolecular condensates can lead to the formation of irreversible fibrils and aggregates that are linked to neurodegenerative diseases. Despite the implications, the interactions underlying such transitions remain obscure. Here we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 78 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…Surprisingly, we found that the aromatic C–H peaks are all negative, which starkly contrasts the variety of the molecular orientation of the studied benzene derivatives. Note that the negative ∼3050–3100 cm –1 Im­(χ YYZ (2) ) peak appears not only for the pure organic solvents of the benzene derivatives but also for benzene derivatives in water ,,, and proteins in water, ,,, indicating that the negative peak is rather universal, independent of the orientation of molecules. Our result clearly suggests a large quadrupole contribution in the aromatic C–H stretching mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we found that the aromatic C–H peaks are all negative, which starkly contrasts the variety of the molecular orientation of the studied benzene derivatives. Note that the negative ∼3050–3100 cm –1 Im­(χ YYZ (2) ) peak appears not only for the pure organic solvents of the benzene derivatives but also for benzene derivatives in water ,,, and proteins in water, ,,, indicating that the negative peak is rather universal, independent of the orientation of molecules. Our result clearly suggests a large quadrupole contribution in the aromatic C–H stretching mode.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, if a signal is dominated by the quadrupole contribution, the information on the orientation of the interfacial molecule cannot be accessed. The origin of the HD-SFG signal of benzene has been extensively discussed in the literature because the Im­(χ (2) ) signal has an aromatic C–H stretching peak despite benzene having no apparent transition dipole moment. In contrast, the origin of the aromatic C–H mode of benzene derivatives in the Im­(χ (2) ) response has not been explored, presumably because of the apparent dipole moment (see Figure ). However, the data published so far commonly show a negative aromatic C–H stretching peak, ,, questioning whether the benzene derivative aromatic C–H stretching mode reflects the molecular orientation.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate how the identity of polar residues affects LST, we tested the ability of FUS variants to aggregate as a function of time. We used both quiescent conditions and shaking that generates shear and disruption at phase interfaces that can nucleate aggregation 72,73 , monitoring the onset and morphology of the aggregation over a 24 hour time course using DIC microscopy (Fig. 5a, left).…”
Section: Liquid-to-solid Transition Is Dependent On Non-tyrosine Pola...mentioning
confidence: 99%
“…Fused in sarcoma (FUS) is an RNA/DNA binding protein and is associated with some intracellular processes such as transcription regulation, RNA splicing, and mRNA transportation. , Many studies have shown that FUS protein undergoes phase separation, a transition from the dispersed state to droplets, gel, or fibrillary gel as FUS contains the low complexity domain (LCD), which tends to lead to multivalent interactions of the proteins. The abnormal phase separation of FUS is involved with the development of neurodegenerative diseases such as familial amyotrophic lateral sclerosis (ALS-FUS). , In addition, FUS and two other proteins of the common protein family (FET family) are codeposited in the cytoplasm of a subset of patients with frontotemporal lobar degeneration (FTLD-FUS) .…”
Section: Introductionmentioning
confidence: 99%